2016
DOI: 10.3390/risks4020010
|View full text |Cite
|
Sign up to set email alerts
|

Telematics and Gender Discrimination: Some Usage-Based Evidence on Whether Men’s Risk of Accidents Differs from Women’s

Abstract: Pay-as-you-drive (PAYD), or usage-based automobile insurance (UBI), is a policy agreement tied to vehicle usage. In this paper we analyze the effect of the distance traveled on the risk of accidents among young drivers with a PAYD policy. We use regression models for survival data to estimate how long it takes them to have their first accident at fault during the coverage period. Our empirical application with real data is presented and shows that gender differences are mainly attributable to the intensity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 12 publications
(11 reference statements)
6
42
0
Order By: Relevance
“…The same authors (Ayuso et al 2016a) conclude that the observed differences in gender are largely attributable to the intensity of vehicle usage: while gender has a significant effect in explaining the time elapsed until the first accident, it has no longer effect when the average daily distance traveled is introduced into the model. Therefore, the authors conclude that discrimination based on gender is not necessary if telematics provide enough information on driving patterns (see Ayuso et al 2016b). This same conclusion is also obtained by Verbelen et al (2017) using a Belgian database.…”
Section: Potential New Research Fieldsupporting
confidence: 65%
“…The same authors (Ayuso et al 2016a) conclude that the observed differences in gender are largely attributable to the intensity of vehicle usage: while gender has a significant effect in explaining the time elapsed until the first accident, it has no longer effect when the average daily distance traveled is introduced into the model. Therefore, the authors conclude that discrimination based on gender is not necessary if telematics provide enough information on driving patterns (see Ayuso et al 2016b). This same conclusion is also obtained by Verbelen et al (2017) using a Belgian database.…”
Section: Potential New Research Fieldsupporting
confidence: 65%
“…Vehicle power presents a positive effect in the traditional model as well in the model that includes all variables, but this is not the case with gender, which is not significant when we include the telematics variables. Indeed, Ayuso et al (2016b) stress the importance of including the new variables of risk exposure and driver behaviour in the new framework that prohibits companies from charging different premiums according to the gender of the driver. Finally, the results are the same for the model with telematics variables and the version with offsets (columns 3 and 4), with a significant influence of the annual distance but also with the percentage of kilometres driven per year over the speed limit and the percentage of urban kilometres driven per year.…”
Section: Resultsmentioning
confidence: 99%
“…This study is interested in predicting Y using the aforementioned covariates. This data set has been extensively studied in Ayuso et al (2014Ayuso et al ( , 2016aAyuso et al ( , 2016b and Boucher et al (2017). Table 1 shows the descriptive statistics for the accident claims data set.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%